Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd006214.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Debridement for surgical wounds

Abstract: Background Surgical wounds that become infected are often debrided because clinicians believe that removal of this necrotic or infected tissue will expedite wound healing. There are numerous methods available but no consensus on which one is most effective for surgical wounds. Objectives To determine the effect of different methods of debridement on the rate of debridement and healing of surgical wounds. Search methods In March 2013, for this third update, we searched the Cochrane Wounds Group Specialised Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The antimicrobial activity of maggots was also observed in the case of bacteria characterized by high resistance to antibiotics, such as Pseudomonas aeruginosa and Staphylococcus aureus [ 37 , 38 , 39 , 44 ]. The elimination of biofilm in these cases is particularly important due to the high resistance to penetration and the action of the human immune system and to antibiotics [ 45 , 46 ]. An important discovery in recent years is the fact that lucifensin with antibacterial properties is not found in the digestive tract of Lucilia sericata but in the salivary glands and the fat body.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of maggots was also observed in the case of bacteria characterized by high resistance to antibiotics, such as Pseudomonas aeruginosa and Staphylococcus aureus [ 37 , 38 , 39 , 44 ]. The elimination of biofilm in these cases is particularly important due to the high resistance to penetration and the action of the human immune system and to antibiotics [ 45 , 46 ]. An important discovery in recent years is the fact that lucifensin with antibacterial properties is not found in the digestive tract of Lucilia sericata but in the salivary glands and the fat body.…”
Section: Discussionmentioning
confidence: 99%
“…For a standardized wound bed preparation, the protocol synthesized by the acronym “TIME” (Tissue management, Inflammation/Infection control, Moisture balance, and Edge of wound), proposed by Leaper et al [ 23 ] and modified by Schultz et al ,[ 24 ] was used. Debridement was done according to Smith et al [ 25 ] [ Figure 1 ]. Empirical and targeted drug therapies were based on WSES/SIS-E consensus.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Sharp, sometimes painful, debridement of SWHSIs was also reported by patients, despite the lack of high-quality evidence to support its use. 75 However, debridement was not measured explicitly as a treatment in the cohort study, so further data are needed on how widespread sharp debridement is as a treatment for SWHSIs. Finally, although our study participants generally viewed NPWT as an effective treatment, they reported various drawbacks, including pain during dressing changes.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%